2010
DOI: 10.1021/ie1008234
|View full text |Cite
|
Sign up to set email alerts
|

A New Pyrolysis of Metal Hydroxide-Mixed Waste Biomass with Effective Chlorine Removal and Efficient Heat Recovery

Abstract: Waste woody biomass samples including poly(vinyl chloride) (PVC), which were mixed with metal hydroxides as additives, were carbonized at 500 °C to investigate the catalytic effect of the additives on pyrolysis products and to elucidate the mechanism of biomass carbonization. The results showed that the yield of char significantly increased, whereas tar evolution was suppressed by the influence of metal hydroxides, even with the coexistence of PVC. Moreover, the interaction behaviors between the biomass struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This indicates that the introduction of CuAl-LDH promotes the linear unsaturated structures to translate into the ring-shaped conjugated structures. After that, more compact char layers are formed through the cross-linking reactions during combustion, which can increase diffusion control of the oxygen and suppress smoke production, leading to an increase in the yields of char and a decrease in the released amount of smoke …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the introduction of CuAl-LDH promotes the linear unsaturated structures to translate into the ring-shaped conjugated structures. After that, more compact char layers are formed through the cross-linking reactions during combustion, which can increase diffusion control of the oxygen and suppress smoke production, leading to an increase in the yields of char and a decrease in the released amount of smoke …”
Section: Resultsmentioning
confidence: 99%
“…After that, more compact char layers are formed through the cross-linking reactions during combustion, which can increase diffusion control of the oxygen and suppress smoke production, leading to an increase in the yields of char and a decrease in the released amount of smoke. 34 3.4. SEM-EDS Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This finding could be explained by the fact that, at lower temperature, the higher release of volatiles during the primary devolatilization catalyzed by the AAEM species is not compensated by [53] observed that the addition of 0.24% and 0.48% of KOH during the co-pyrolysis of mixtures of bio-oil and biomass (aspen wood) at 600°C led to an increase in the mass yield of biochar of 22.3% and 25.2%, respectively. The effect of peak temperature was analyzed by Hayashi et al [54] during the pyrolysis of mixtures of wood and PVC catalyzed by alkaline and alkaline earth metal hydroxides. One of the major findings reported in the study by Hayashi et al [54] was that the increase in char yield was affected by peak temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of peak temperature was analyzed by Hayashi et al [54] during the pyrolysis of mixtures of wood and PVC catalyzed by alkaline and alkaline earth metal hydroxides. One of the major findings reported in the study by Hayashi et al [54] was that the increase in char yield was affected by peak temperature. More in detail and in line with the results reported here, the addition of hydroxides at temperatures of 300 and 400°C led to a decrease in char yield.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, scrupulous attention is paid to environmental protection . From a great number of pollution sources, industrial waste has the most detrimental effect on the environment. , The quantities of such waste production are usually quite high; therefore, it is critical to develop efficient ways of recycling it or reducing the level of its hazardous influence on the environment to permissible values.…”
Section: Introductionmentioning
confidence: 99%